Eutectic Crystallization: Multi‐Step Crystallization of Self‐Organized Spiral Eutectics (Small 8/2020). Issue 8 (24th February 2020) - Moniri, Saman; Bale, Hrishikesh; Volkenandt, Tobias; Wang, Yeqing; Gao, Jianrong; Lu, Tianxiang; Sun, Kai; Ritchie, Robert O.; Shahani, Ashwin J.
Abstract : In article number 1906146, Robert O. Ritchie, Ashwin J. Shahani, and co‐workers investigate the origins of certain eutectics that grow into spiral geometry. The spiral formation follows a two‐step process, wherein the first step is mediated by the low solid–liquid interfacial energy of a precursor phase, and the second step by crystallographic defects on the precursor. The cover features a computed X‐ray nano‐tomography image of spiral eutectics in Mg‐Zn alloy showing multiple spiral eutectic colonies with the eutectic MgZn2 and Zn phases shown in dark and light false colors (image courtesy of H. Bale).